File-based race conditions in UNIX: TOCTOU - Razvan Raducu; Rodríguez, Ricardo J; Álvarez, Pedro J (Jornada de Jóvenes Investigadores del I3A, 2020)
This work presents an introduction to the Time Of Check to Time Of Use (TOCTOU) vulnerability as well as the development of a user-space library that hooks vulnerable system calls and modifies their behavior.